(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the evidence in the literature on the efficacy of pelvic floor muscle training on the sexual function (SF) of men after prostatectomy by an overview of systematic reviews (SR) of randomized clinical trials. The search for studies was conducted in five databases without any language restriction: EMBASE, PUBMED, Science Direct, PEDro, and Cochrane Library. The main results were extracted from the SR by two reviewers, and meta-analysis was performed from the primary studies for the outcomes SF scores and erectile dysfunction. 4 reviews were included in the qualitative synthesis, which involved 8 clinical trials and 891 participants. The reviews had moderate to good methodological quality, but a high overlap of clinical studies was founded. Meta-analysis showed that pelvic floor muscle training improves sexual function scores not in 3 months (p=0.51) but in 6 months (p=0.02) and it did not show efficacy on erectile dysfunction after three (p=0.58) and 12 months (p=0.32). Studies with moderate to good methodological quality demonstrate that pelvic floor muscle training only improve sexual function score in 6 months, but not had efficacy in erectile dysfunction in men after prostatectomy.